In Situ Polymer Graphenization Ingrained with Nanoporosity in a Nitrogenous Electrocatalyst Boosting the Performance of Polymer‐Electrolyte‐Membrane Fuel Cells. Issue 7 (16th December 2016) - Fu, Xiaogang; Zamani, Pouyan; Choi, Ja‐Yeon; Hassan, Fathy M.; Jiang, Gaopeng; Higgins, Drew C.; Zhang, Yining; Hoque, Md Ariful; Chen, Zhongwei
Abstract : Rich, porous graphene frameworks decorated with uniformly dispersed active sites are prepared by using polyaniline as a graphene precursor and introducing phenanthroline as a pore‐forming agent. The unprecedented fuel‐cell performance of this electrocatalyst is linked to the graphene frameworks with vast distribution of pore sizes, which maximizes the active‐sites accessibility, facilitates mass‐transport properties, and improves the carbon corrosion resistance.